EMPLOYER BRANDING, SOCIAL MEDIA, AND GENERATION Z'S JOB APPLICATION INTENTIONS: THE MEDIATING ROLE OF CORPORATE REPUTATION - Listika; Usman Usman (Jurnal Multidisipliner Kapalamada, 2026)
This study aims to analyze the influence of employer branding and social media use on Generation Z’s job application intention, with corporate reputation serving as a mediating variable among fresh graduates of the Faculty of Social and Political Sciences, Halu Oleo University. The study employed a quantitative approach using purposive sampling. The population consisted of 1,039 fresh graduates who graduated in 2025, with a sample of 289 respondents determined using the Slovin formula. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4. The results indicate that employer branding and social media use have a positive and significant effect on corporate reputation and job application intention. Corporate reputation also has a positive and significant effect on job application intention and partially mediates the influence of employer branding and social media use on job application intention, thereby strengthening the company's attractiveness among Generation Z job seekers.